The Role of Female Workers as Agents of Household Economic Recovery in Sakra Selatan Village: An Islamic Economics Perspective - Jalil, Muh. Rabbul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Abstract This paper aims to elaborate on gender equality between men and women in the economic sector. They have equal status and conditions to fully realise their human rights and potential for the proportional integrity and sustainability of the household economy. The method used in this paper is field research qualitative with a case study approach. The data used in this paper are sourced from, first, primary data related to women involved in migrant worker activities, collected through observation, interviews, and documentation. Second, secondary data in the form of books, articles, and journals relevant to the object or theme of this study. The results of this paper show that Islamic economics, with reference to the basic principles of maslahat, provides legislation for women to become part of economic actors in the field of female labour. Based on field data, the involvement of wives who work as female labourers is directly proportional to an increase in family income, thus having a positive effect on the economic resilience of households in the village of Sakra Selatan.